Newman and the Alexandrian fathers: shaping doctrine in nineteenth-century England - King, Benjamin John ca. 20./21. Jh. (Changing paradigms in historical and systematic theology, 2009)
John Henry (later Cardinal) Newman is generally known to have been devoted to reading the Church Fathers. In this volume, Benjamin King draws on archive as well as published material to explore how Newman interpreted specific Fathers at different periods of his life. King draws connections between the Alexandrian Fathers Newman was reading and the development of his thought. This analysis shows that it was events in Newman's life that changed his interpretation of the Fathers, notthe interpretation of the Fathers that caused Newman to change his life. King argues that Newman tailored his readi